Assessment of the quality of reporting in studies of acupuncture for patients with cancer using the STRICTA guidelines. Issue 4 (August 2019) - Hughes, John G; Lewith, George; MacPherson, Hugh; Witt, Claudia M; Cummings, Mike; Fisher, Peter
Introduction: There has been a burgeoning of research evaluating acupuncture for various symptoms of cancer and the side-effects associated with its treatment. A systematic review was conducted to examine the quality of reporting in published studies of acupuncture in cancer according to the STRICTA (STandards for Reporting Interventions in Clinical Trials of Acupuncture) guidelines. Methods: Systematic review of published research of acupuncture for symptoms of cancer and the side-effects associated with its treatment. Databases searched were: Medline, CINAHL, Cochrane (all databases), Scopus, and PubMed from their inception to December 2014. Clinical trials, pilot/feasibility studies, observational studies, and case studies were included. Only full journal papers published in English were included. The quality of reporting was evaluated using STRICTA guidelines. Each included paper was assessed by two independent reviewers, with disagreements adjudicated by a third reviewer. Results: 88 papers were identified which met the inclusion criteria. The median number of STRICTA items reported in trials with a control or comparator arm (n=47) was 14 out of 17 (range 8 to 17, IQR 4). For studies without a control or comparator arm the median was 11 out of a possible 15 (range 5 to 15, IQR 3). Key weaknesses in reporting included details of other components of treatments, and details of the acupuncturist administering treatments. Conclusions: Despite the widespread use of the STRICTA guidelines in acupuncture research, adherence remains poor for a few specific items. Further research is required to explore the reasons why authors fail to report those items, and to develop strategies to improve the adherence to the guidelines.